2018
DOI: 10.7759/cureus.2597
|View full text |Cite
|
Sign up to set email alerts
|

Wernicke’s Encephalopathy as a Rare Complication of Hyperemesis Gravidarum: A Case Report and Review of Literature

Abstract: Wernicke's encephalopathy (WE) is a rare neurological syndrome that presents in the setting of thiamine deficiency. Though alcoholism is the most common cause of this condition, a few other etiologies include malnutrition from other causes, hemodialysis, and hyperemesis gravidarum. In this case report, we aim to report a case of a young woman who developed WE in the setting of hyperemesis gravidarum (HG) that improved with thiamine replacement. This manuscript details her presentation and clinical examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Visual symptoms have been described as a prodromal characteristic of WE in other populations that have forms of malnutrition, such as anorexia nervosa [165], dietary issues [168,169], and some cancers [170]. In alcoholics, patients with WE often lack any awareness of their own illness, reducing the chance they will present to emergency services with visual disturbances [141,144]. In clinical practice, visual disturbance in HG specifically warrants attention for possible thiamine deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Visual symptoms have been described as a prodromal characteristic of WE in other populations that have forms of malnutrition, such as anorexia nervosa [165], dietary issues [168,169], and some cancers [170]. In alcoholics, patients with WE often lack any awareness of their own illness, reducing the chance they will present to emergency services with visual disturbances [141,144]. In clinical practice, visual disturbance in HG specifically warrants attention for possible thiamine deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is mainly clinical and confirmed by characteristic MRI findings and dramatic clinical response to thiamine. A high index of suspicion is required for early diagnosis of WE in HG, and early initiation of thiamine supplementation is essential [ 8 - 10 ]. Bonucchi et al have reported a case where the hypermetabolic state from thyrotoxicosis in a patient with HG contributed to the development of WE.…”
Section: Discussionmentioning
confidence: 99%
“…[11,12] Moreover, has some catastrophic consequences such as central pontine myelinolysis, Wernicke's encephalopathy, vasospasm of cerebral arteries, rabdomyolysis, coagulopathy, and maternal and fetal death. [13][14][15] While HG generally occurs between the 8 th and 10 th gestational weeks of pregnancy, in 10% of all HG cases, it persists until the birth. [12] Previous HG history, multiple and molar pregnancy, gestational trophoblastic neoplasia, hyperthyroidism, gastrointestinal disorders, female offspring, and psychiatric disorders are the main risk factors for HG.…”
mentioning
confidence: 99%